Unidad didáctica: un acercamiento intertextual al libro y la película satanás para mejorar la habilidad inferencial en estudiantes de noveno grado (2016)
This project arises from concern about the low levels of inferential reading comprehension evidenced during the pedagogical practice exercise I at the Gustavo Restrepo District Educational Institution, specifically in the ninth grades of the afternoon session. After several application exercises in which they had to perform reading comprehension, it was found that the students did not understand elementary instructions, for example, they did not get an effective answer, in terms of, that inferential reading seeks for students to understand what is not implicit in the text, therefore, they expressed disorientation, confusion and apathy towards reading.